2004
DOI: 10.1213/01.ane.0000133001.42742.49
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transesophageal Echocardiography in Rapid Diagnosis and Treatment of Migratory Tumor Embolus

Abstract: Transesophageal echocardiography (TEE) is sometimes used in renal cell carcinoma excision for evaluating the extension of tumor in the inferior vena cava (IVC), characterizing the tumor anatomy, monitoring the tumor during surgical mobilization, and assessing cardiac function. Although the risk for embolization is small, when embolization does occur, its consequences can be catastrophic. In this case report, we describe the crucial role of TEE in diagnosing an intraoperative migratory embolus from the IVC to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…One institution recommended TEE only be available for all higher staged tumors, even if thought to be organ‐confined, to help prevent risk of tumor embolization if incidentally present in the venous system. This same group also routinely used intraoperative TEE for all tumors with known IVC involvement irrespective of level . No matter the preoperative plan, it is our recommendation that any institution attempting resection of RCC with tumor thrombus have the capability to obtain an intraoperative TEE assessment quickly should the clinical need arise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One institution recommended TEE only be available for all higher staged tumors, even if thought to be organ‐confined, to help prevent risk of tumor embolization if incidentally present in the venous system. This same group also routinely used intraoperative TEE for all tumors with known IVC involvement irrespective of level . No matter the preoperative plan, it is our recommendation that any institution attempting resection of RCC with tumor thrombus have the capability to obtain an intraoperative TEE assessment quickly should the clinical need arise.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies reported preoperative imaging within 4 weeks of surgery, but many are now recommending reimaging within seven to 14 days of surgical extirpation . The reason for this is that tumor thrombi can grow and propagate quickly, and there are many examples throughout the literature where preoperative imaging did not well‐represent the degree of tumor thrombus compared to the surgical resection specimen . For example, it has been reported that intraoperative TEE revealed findings not seen on a TTE from just 2 days prior to surgery.…”
Section: Preoperative Imaging As Guidance For Operative Planningmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Other similarly favorable outcomes were subsequently reported. [14][15][16] Investigators have found TEE to be accurate in monitoring intraoperative embolic phenomena during tumor manipulation, 17 evaluating IVC tumor extension, 18 recognizing residual tumor after attempted resection, 19 and evaluating preload and cardiac function during IVC clamping. Oikawa and colleagues 20 described the additional use of intraoperative TEE to position an intracaval balloon above the tumor thrombus, thus enabling resection without the need to mobilize the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports have highlighted the role of the TEE in patients undergoing renal cell carcinoma excision utilizing cardiopulmonary bypass. 1,2 In this case, TEE imaging provided real-time guidance to surgical excision of a large renal cell carcinoma.…”
mentioning
confidence: 87%